Pengaruh Inflasi, Suku Bunga, dan PDB Terhadap Saham Perbankan - Vista Yulianti; Erlina Widayanti Djatnicka (Prosiding SEMANIS: Seminar Manajemen Bisnis, 2023)
The purpose of this study was to determine the effect of inflation, interest rates and GDP on the stock price of Bank BCA. The object of this study is BCA Bank Shares. The research method used in this study is the effect of inflation, interest rates and GDP on BCA Bank stock prices using validity, reliability and hypothesis analysis tests. The results obtained from this study are the T test showing that inflation has no effect on BCA stock prices, interest rates have a significant negative effect on BCA shares, and GDP has a significant positive effect on BCA shares. The results of the F test show that simultaneously inflation, interest rates and GDP have a significant positive effect on BCA shares